ANALISIS KASUS DEMAM BERDARAH DENGUE BERBASIS BEBERAPA INDIKATOR DI KABUPATEN SLEMAN - Wahyuni, Rizqi Intan; Rubaya, Agus Kharmayana; Yamtana, Yamtana (Universitas Islam Negeri Alauddin Makassar, 2024)
Introduction: DHF is an endemic disease in Sleman Regency. Kapanewon or District in Sleman Regency has not reached national target (IR 49 per population). Geographic Information System (GIS)-based mapping hopefully can help produce the right policies in controlling DHF cases in Sleman Regency. Objective: This research aims to descriptively understand the distribution of DHF cases related to Larvae-free Index, Healthy Houses, Clean and Healthy Life Behavior in the household, and population density in Sleman Regency in 2015-2019 with GIS-based mapping. Methods: This research aims to descriptively understand the distribution of DHF cases related to Larvae-free Index, Healthy Houses, Clean and Healthy Life Behavior in the household, and population density in Sleman Regency in 2015-2019 with GIS-based mapping. This descriptive research using Ecological Study design with retrospective approach, through GIS-based mapping in overlays form. It used total sampling of 17 Kapanewon in Sleman Regency. Variables used are secondary data for 2015-2019 obtained from Health Department and Civil Registry Department of Sleman Regency. Results: DHF incidence in Sleman Regency for 5 years (2015-2019) has fluctuated and tends to occur a lot in Kapanewon which close to Yogyakarta City, Bantul Regency, and Kulon Progo Regency. Map overlay shows Larvae-free Index and population density related to DHF cases. Healthy Houses and Clean and Healthy Life Behavior in the household not related to DHF cases in Sleman Regency. Chi-square test results show that population density related to DHF cases. Meanwhile, Larvae-free Index, Healthy Houses, and Clean and Healthy Life Behavior in the household not related to DHF cases in Sleman Regency. Conclusion: Based on descriptive analysis, Larvae-free Index and population density related to DHF cases in Sleman Regency in 2015-2019.